1994
DOI: 10.1136/jcp.47.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin expression and acetowhite change in cervical epithelium.

Abstract: Aim-To investigate the distribution of cytokeratins 10, 13, 14 and 19 in biopsy specimens taken from acetowhite and non-acetowhite areas of the cervix. Method-Cervical biopsy specimens were taken from both acetowhite and non-acetowhite areas from 44 patients who presented with abnormal cervical cytology. The specimens were snap frozen in liquid nitrogen and multiple sections taken from each specimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
7

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 5 publications
0
19
0
7
Order By: Relevance
“…We found that the late-versus early passage W12 cells cultured on organotypic rafts exhibited abnormal features resembling those seen in multistage progression of cervical carcinoma (30). The architecture of the raft tissue was analyzed by staining for keratin 19 (CK-19) and CK-10.…”
Section: Expression Analysis Of Jagged1 and Manic Fringe In Caski Celmentioning
confidence: 99%
“…We found that the late-versus early passage W12 cells cultured on organotypic rafts exhibited abnormal features resembling those seen in multistage progression of cervical carcinoma (30). The architecture of the raft tissue was analyzed by staining for keratin 19 (CK-19) and CK-10.…”
Section: Expression Analysis Of Jagged1 and Manic Fringe In Caski Celmentioning
confidence: 99%
“…These calculations were done analogously to those for the cytoplasm described in Eqs. (9) to (11). For MR1 cells, the scattering efficiencies were about 8% higher for the masks covering the entire nucleus, indicating that stronger scattering was occurring from LysoSensor stained areas.…”
Section: Changes In Light Scattering When Acetic Acid Is Appliedmentioning
confidence: 93%
“…11 The strong increase in light scattering for MR1 cells which do not express cytokeratins demonstrates that cytokeratins are not critical for acetowhitening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism causing the acetowhitening of the epithelium is not yet clear; it has been associated with a sexually transmitted agent [13], very likely a virus, that produces an increasing expression of proteins, such as cytokeratin 10 [18], and areas of high nuclear density. Our observations seem to suggest that high-risk HPV types might induce changes in the infected cells that produce a reaction with acetic acid.…”
mentioning
confidence: 99%